Medicinal plants traded in Hakka communities of southeastern Guangxi, China - Yongqing Liufu; Yaozhang Xie; Min Shao; Qiongyao Fu; Zhongxin Duan; Dipak Khadka; Binsheng Luo (Journal of Ethnobiology and Ethnomedicine, 2025)
Abstract Background The Hakka are one of the major subgroups of the Han  Chinese in China, with a unique migration history and a rich traditional medicine system. Traditional markets serve as centers for the exchange of Hakka medicinal culture and play a vital role in maintaining residents’ health. However, medicinal plants traded in traditional Hakka markets have not been documented in southeastern Guangxi, China. Methods We documented the medicinal plants traded in the market of Hakka communities in southeastern Guangxi, China, by interviewing 106 traditional shopkeepers. Relative frequency of citation (RFC) and relative importance value (RI) were used to evaluate the most medicinal plants traded in the market of Hakka communities, and the Jaccard index of similarity (JI) was used to assess the similarity of plants used by Hakka from different communities in China. Results We documented 305 medicinal plant species, with the Fabaceae family being the most represented (27 species). In terms of life form, herbs constituted the largest group, accounting for 130 species (42.62%). Regarding plant parts used, leaves were the most commonly utilized, reported for 122 species (32.36%). The recorded medicinal plants exhibit 63 therapeutic effects and are used to treat 117 ailments across 14 disease categories. The most frequently cited medicinal use was for the treatment of physical trauma (126 species, 41.31%), followed by digestive disorders (96 species, 31.47%), skin diseases (90 species, 29.51%), and detoxification (79 species, 25.90%). Twenty-eight plant species had a relative citation frequency (RFC) greater than 0.5, and 23 species had a relative importance (RI) value of ≥ 1.25. A comparative analysis with medicinal plants recorded in Hakka communities of Guangdong and Ganzhou revealed some similarities, with Jaccard index (JI) values of 0.10 and 0.06, respectively. Conclusion The local shopkeepers of traditional markets in Hakka communities in southeastern Guangxi are prosperous in their knowledge of medicinal plant use. We recommend conserving these medicinal plants of local people by promoting the traditional market, which fosters people's livelihood through income generation and supports the sustainability of the traditional knowledge system.